The relationship between sleep disturbances, depression and anxiety in differentiated thyroid cancer patients during radioiodine (131I) therapy: a longitudinal observational study - Huang, Wanmin; Zheng, Yusheng; Guo, Jinyan; Luo, Chunliu (Frontiers in Endocrinology, 2026)
BackgroundThe temporal dynamics of sleep disturbances following radioactive iodine (RAI) therapy for differentiated thyroid cancer (DTC), along with their underlying mechanisms and associated factors, remain poorly understood. This gap underscores the need for longitudinal investigations.MethodsWe conducted a longitudinal study of 160 DTC patients from Guangdong Southern Teaching Hospital. Self-assessment scales were used to assess patients’ knowledge of the purpose of ¹³¹I therapy, depression, anxiety symptom and sleep assessment scales were used to assess with the Pittsburgh Sleep Quality Index, Insomnia Severity Index, Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS). Assessments were conducted at three time points: pre-therapy, peri-therapy (during hospitalization), and post-therapy.ResultsOf the 160 patients, 148 completed the study (53 males [35.8%]; 95 females [64.2%]). Risk factors associated with sleep disorders included anxiety, snoring, educational level, and work/study-related stress. Longitudinal trajectory analysis revealed nonlinear trends: the incidence of sleep disorders (35.8% → 52.9% → 32.6%), anxiety symptoms (23.6% → 40.7% → 14.0%), and depressive symptoms (47.3% → 56.4% → 33.3%) all increased initially before declining.ConclusionWith increasing treatment duration, the incidence of sleep disorders, anxiety, and depression initially rose and subsequently declined. Sleep quality reached its lowest point at the end of treatment, whereas anxiety and depression levels peaked one month post-therapy before decreasing to levels below the pre-treatment baseline.